Pressure tuning of intrinsic and extrinsic sources to the anomalous Hall effect in CrGeTe_{3} - Gili Scharf; Daniel Guterding; Bar Hen; Paul M. Sarte; Brenden R. Ortiz; Gregory Kh. Rozenberg; Tobias Holder; Stephen D. Wilson; Harald O. Jeschke; Alon Ron (Physical Review Research)
The integrated Berry curvature is a geometric property that has dramatic implications for material properties. This study investigates the integrated Berry curvature and other contributions to the anomalous Hall effect in CrGeTe_{3} as a function of pressure. The anomalous Hall effect is absent in the insulating phase of CrGeTe_{3} and evolves with pressure in a domelike fashion as pressure is applied. The dome's edges are characterized by Fermi surface deformations, manifested as mixed electron and hole transport. We corroborate the presence of bipolar transport using ab initio calculations, which also predict a nonmonotonic behavior of the Berry curvature as a function of pressure. Quantitative discrepancies between our calculations and experimental results indicate that additional scattering mechanisms, which are also strongly tuned by pressure, contribute to the anomalous Hall effect in CrGeTe_{3}.